A Case of Hydatid Cyst of Thyroid Gland - Dey, Arpan Kumar; Mandal, Pijush Kanti; Dutta, Agnibha; Pramanik, Subhraprakash; Maji, Saurabh; Chakraborti, Nabonita; Dasgupta, Somnath (Asian Journal of Medical Sciences, 2013)
Hydatid cyst may be found in almost any part of the body, but most often in the liver and the lungs. Other organs affected occasionally include the brain, muscle, kidney, heart, pancreas, adrenal, and thyroid gland. Hydatidosis located in the thyroid is an infrequent finding, even in endemic regions. This report documents a rare case with a cystic nodule in the thyroid detected by ultrasonography. The patient was a 30-year-old woman with an euthyroid multinodular goitre. Ultrasonography revealed a cystic nodule, and the ultrasonic appearance of the cyst liquid showed multiple echoes, suggesting that the nodule could be a hydatid cyst. The histopathologic examinations confirmed this to be a primary hydatid cyst of thyroid. During the differential diagnosis of the cystic thyroid lesions, hydatid disease of the thyroid gland should be considered in endemic areas. Chemotherapy is necessary to avoid recurrence. DOI: http://dx.doi.org/10.3126/ajms.v5i2.8830 Asian Journal of Medical Science, Volume-5(2) 2014: 143-145